Identification of a Putative Enhancer RNA for EGFR in Hyper-Accessible Regions in Esophageal Squamous Cell Carcinoma Cells by Analysis of Chromatin Accessibility Landscapes - Choi, Sangyong; Sathe, Adwait; Mathé, Ewy; Xing, Chao; Pan, Zui (Frontiers in Oncology, 2021)
Abnormal genetic and epigenetic modifications play a key role in esophageal cancer. Using Assay for Transposase-Accessible Chromatin using sequencing (ATAC-seq), this study compared chromatin accessibility landscapes among two esophageal squamous cell carcinoma (ESCC) cell lines, KYSE-30 and KYSE-150, and a non-cancerous esophageal epithelial cell line, HET-1A. Data showed that hyper-accessible regions in ESCC cells contained genes related with cancer hallmarks, such as epidermal growth factor receptor (EGFR). Multi-omics analysis and digital-droplet PCR results demonstrated that several non-coding RNAs in EGFR upstream were up-regulated in ESCC cells. Among them, one appeared to act as an enhancer RNA responsible for EGFR overexpression. Further motif analysis and pharmacological data suggested that AP-1 family transcription factors were able to bind the hyper-accessible regions and thus to regulate cancer cell proliferation and migration. This study discovered a putative enhancer RNA for EGFR gene and the reliance of ESCC on AP-1 transcription factor.